Harper's illustrated biochemistry - Murray, Robert K. (Robert Kincaid) 1932- ("A Lange medical book", 2009)
With a combination of case studies, discussions of biochemical diseases, updated clinical information, and frequent revision, this is an indispensable book for students of biochemistry.